Analisis Enterprise Resource Planning dalam Persediaan Material dengan Metode Manufacturing Resource Planning Menggunakan Software Odoo 13 Manufacturing (Studi Kasus PT. Yuasa Battery Indonesia) - Kuntoro, Kuntoro; Susanto, Agung Budi; Kurnia, Dadang (Teknik Informatika Universitas Pamulang, 2021)
PT. Yuasa Battery Indonesia is a manufacturing company engaged in the manufacture of batteries for motor vehicles, both cars and motorcycles. The production system in this company is make to order. The production process that occurs is that the recording of production activities is still carried out in their respective work sections such as manufacturing, inventory, purchasing so that the information needed for the production line is slow and inaccurate which results in the production plan not being achieved. The purpose of this research is to integrate data and information in all lines of the company so that the constraints faced by the company can be overcome. The material flow for the production process is controlled using the Material Requirement Planning method while the software used to integrate data and information in the production line is Odoo 13 manufacturing. The results showed an increase in productivity from the planned production of 128,387 pcs, 128,381 pcs with and 6 pcs was achieved and the percentage of production achievement was 100% and users accepted the implementation of Odoo 13 with an average test result of 82.3%.